The mediating effect of attitude on e-wallet acceptance among Malaysians - Abdul Kadir, Hasnah; Ismail, Rizalawati; Wok, Saodah (Centre of Research in Media and Communication, UKM, 2019)
Malaysia is moving towards a cashless society. The latest trend in a cashless society is e-Wallet, which has the ability to store personal information as well as financial status. The e-wallet can efficiently replace the physical wallet (cash). The implementation of online lnternet banking for a financial transaction is the starting point of e-Wallet in Malaysia. h 2A17, e-Wallet is introduced to the public. This study tries to gauge the extent of e-Wallet usage in Malaysia. The objectives of the study are to (1) determine the level of usage, perceived usefulness, perceived ease of use, media influence, social influence and attitude in using e-Wallet; (2) analyze the relationship between e-Wallet usage with internal and external factors; and (3) test mediating effect of attitude in using e-Wallet on the relationship between usage, internal factors and extemal factors. The study uses a quantitative research design using a survey method with the questionnaire as the research instrument. A total of 436 respondents participated in the study. The study uses Technological Accepaance Model (TAtvI) to test for the mediating effect. The findings show that perceived ease of use is the highest level rated compared to other variables. The relationship betw'een e-Wallet usage with the internal and external factors are all significant and positive. Furthermore. the attitude partially mediates the relationship between e-Wallet usage, intemal factors and external factors. Hence, all hypotheses constructed are supported and TAM applies to the study of e- Wallet.